Formulation of water-dispersible hydrophobic compound nanocomplexes with polypeptides via a supramolecular approach using a high-speed vibration milling technique. Issue 49 (8th November 2022) - Kawamura, Shogo; Kawasaki, Riku; Hino, Shodai; Yamana, Keita; Okuno, Masafumi; Eto, Takuro; Ikeda, Atsushi
Abstract : Polypeptides were used to solubilize functional hydrophobic molecules via a high-speed vibrational milling method. Abstract : Polypeptides were used to solubilize functional hydrophobic molecules via a high-speed vibrational milling method. Poly-l -lysine and poly-γ-glutamic acid, which are polypeptides, were able to prepare more highly concentrated water-dispersible complexes of hydrophobic compounds, including fullerenes, organic dyes, and porphyrin derivatives, than conventional water solubilizers, such as cyclodextrins and pullulan. In addition, the polypeptide systems endowed the complexes with long-term stability and resistance against thermal stress, which is advantageous for industrial applications. Furthermore, complexes of polypeptides and porphyrin derivatives showed a photodynamic activity against cancer cells, and the current system improved the dispersibility and storability of guest molecules without compromising their functionality.